The oldest lower Upper Cretaceous plesiosaurs (Reptilia, Sauropterygia) from southern Patagonia, Argentina - O'gorman, Jose Patricio (2010)
Plesiosaurs are recorded for the first time from the lower section of Mata Amarilla Formation, Santa Cruz Province, Patagonia, Argentina. The stratigraphic succession consists of mudstones and siltstones interbedded with medium to fine-grained sandstone, deposited in a littoral environment during the Cenomanian-Santonian; therefore the material is the oldest record of plesiosaurs from the lower Late Cretaceous rocks of Argentina. The remains include teeth, some vertebrae, and one propodium assigned to Elasmosauridae indet. and Plesiosauria indet. The status of Polyptychodon patagonicus Ameghino, 1893, as well as its stratigraphic position are discussed, leading to the conclusion that the material described by Ameghino is probably from the Mata Amarilla Formation and can only be referred to Plesiosauria indet. Analysis of sedimentologic features suggests that the material described here was deposited in an estuarine environment, strongly influenced by tides. The characters of the inferred environment are consistent with the type of preservation of the materials